Household Level Water Recycling for Non-Potable Reuse: A Study on Mujgunni Residential Area of Khulna City, Bangladesh (Journal of Bangladesh Institute of Planners, 2015)
The paper examined the possibility and of reusing household’s grey water for non-potable uses as a means for reducing fresh water demand. The study was done in one of the planned residential areas of Khulna city where water demand and consumption is higher than other haphazardly grown areas. The study used two databases and other secondary materials, collected from relevant organizations. In addition personal communication has been made with concerned personnel. The study found that the residence of the study area get 46% supply water compared with only 20% in the whole city. Availability of water increased water consumption up to 300 litres per day per household. A significant amount of water (90%) is used for bathing, washing and cooking. Both the shower and kitchen water goes straight to drainage system to be more polluted with other toxic wastes. On the other hand, supply system is entirely based on ground water and absence of demand management techniques, over-extraction of ground water has been observed. Khulna city and surroundings have been facing salinity and arsenic contaminations in ground water, making it too vulnerable to provide fresh water to its 1.5 million citizens in coming years. Water treatment still remains uncovered in Bangladesh and authorities repeatedly had gone for capital intensive ground water extraction. Keeping in mind the ease, affordability and available technology, dual-reticulated recycling method is thus advised where the grey water will go again for toilet flushing and gardening after minimal treatment. It was assumed that the system will bring the half of the household waste water into use which will eventually reduce demand for fresh water.Journal of Bangladesh Institute of Planners, Vol. 8, Dec 2015, pp. 93-102